Secreted ADP Plays a Central Role in Thrombin-induced Phospholipase D Activation in Human Platelets - Martinson, Elizabeth A.; Scheible, Stephan; Marx-Grunwitz, Alexandra; Presek, Peter (Thrombosis and Haemostasis, 1998)
Thrombin and other agonists that induce secretion and aggregation in human platelets also activate phospholipase D (PLD), but the signaling cascade leading to activation of PLD in human platelets is not yet clear. We have determined that apyrase, which scavenges ADP secreted during platelet activation, is able to block or reduce the PLD activation stimulated by low (0.1 U/ml or less) or high (0.3-1.0 U/ml) concentrations of thrombin, respectively. Neither ADP (up to 100 μM) nor its more potent analogue 2-methylthio-ADP (up to 100 μM), however, are able to stimulate PLD alone, and even the addition of fibrinogen, which results in platelet aggregation, is not sufficient for PLD activation. In contrast, ADP is able to stimulate PLD in the presence of low concentrations of thrombin that alone have little or no effect, suggesting ADP may play an amplifying role in platelet PLD activation. This hypothesis is supported by the finding that the purinergic receptor antagonist ARL 66096, an ATP analogue, reduces in a concentration-dependent fashion the PLD response to thrombin (IC50 = 28 nM with 0.1 U/ml thrombin). ARL 66096 also abolishes the PLD activation by ADP observed in the presence of low concentrations of thrombin, confirming that the antagonist inhibits an ADP-dependent component of the response. In addition, the thromboxane A2 receptor agonist U46619 activates PLD, and this response is markedly reduced by ARL 66096. Concomitantly, phosphorylation of the protein kinase C substrate pleckstrin in response to thrombin or U46619 is partially or totally inhibited by ARL 66096, respectively, consistent with ADP stimulation of protein kinase C being involved in the PLD response to these agonists. Based on these findings, we conclude that ADP secretion and activation of purinergic ADP receptors is an important amplification mechanism in the signal transduction pathways leading to PLD activation in human platelets.